Improved convolutional neural networks for aircraft type classification in remote sensing images - Alraba'nah, Yousef; Hiari, Mohammad (Institute of Advanced Engineering and Science, 2025)
With the exponential growth of available data and computational power, deep convolutional neural networks (CNNs) have become as powerful tools for a wide range of applications, ranging from image classification to natural language processing. However, during last decade, remote sensing imagery has emerged as one of the most prominent areas in image processing. Variations in image resolution, size, aircraft types and complex backgrounds in remote sensing images challenge the aircraft classification task. This study proposes an effective aircraft classification model based on CNN architecture. The CNN network architecture is improved to achieve more accuracy rate and to avoid overfitting and underfitting problems. To validate the proposed model, a new public aircraft dataset called multi-type aircraft remote sensing images 2 (MTARSI2) has been used. Through an analysis of existing methodologies and experimental validation, the model shows the superior performance of the proposed CNN model in comparison to state-of-the-art deep learning approaches.